Complementary consultations in Iranian infertility treatment centers: a web-based qualitative study - Samira Katebi; Mansour Deilami; Zahra Mosalanezhad; Tayyebeh Zarei; Mehrdad Malekshoar; Somayeh Mehrpour; Hajar Taghizadeh; Roohie Farzaneh; Pourya Adibi; majid vatankhah; farideh mogharab (Mashhad University of Medical Sciences, 2023)
Introduction: Currently, the advancement of knowledge and technology in assisted reproductive technologies (ARTs) has caused infertile couples to look at it less as a crisis; however, there is still a need for awareness and counseling in the field of assisted reproductive treatments. Considering the people's interest in receiving health information from online content, the present study was conducted with aim to investigate the websites of infertility treatment centers in the country as a source of information for providing services in order to evaluate and analyze the amount of complementary counseling. Methods: This research is a web-based content analysis that was searched using Google's advanced search tool between August and September 2023 with the keywords of infertility treatment center, clinic, specialized service center and similar words. The content analysis was done using the observation checklist for the objective evaluation of the variables and as a census from the official website of the infertility treatment centers of the country. Results: In this study, 37 websites of infertility treatment centers and clinics were first surveyed, of which 25 met the inclusion criteria. Of these, 18 cases (72%) provided initial explanations of counseling, 15 websites (60%) explained how to provide counseling services, and 16 cases (64%) had stated the types of counseling provided by the center. Also, 17 websites (68%) provided educational materials in the field of infertility treatment and 18 (72%) provided communication facilities for their contacts. The websites that had their own success rate, disclaimer for providing consulting services and facilities for viewing users' views were less than 35%. Conclusion: Since the official websites of the centers are a capacity to introduce services and provide awareness, despite the importance of counseling in the decision-making of clients, the full capacity of websites in this field has not been used yet.